Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam Melalui Model Pembelajaran Discovery Learning di Kelas IV SDN 058101 Sumber Jaya - Winarsih Winarsih (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study is motivated by the low learning outcomes of students in Islamic Religious Education at SD Negeri 058101 Sumber Jaya, attributed to less varied teaching methods that fail to engage students effectively. The aim of this research is to explore and analyze the implementation of the Discovery Learning model in enhancing students' learning outcomes. The research method used is Classroom Action Research (CAR) conducted in two cycles, with 26 students as subjects. Data collection was carried out through tests and observations. The results showed a significant improvement in students' learning outcomes, with the completion percentage rising from 45.83% in the pre-cycle to 79.16% in Cycle I, and reaching 91.66% in Cycle II. The application of the Discovery Learning model proved effective in increasing student engagement and understanding of the material, as well as helping them develop critical and reflective thinking skills. This study concludes that the implementation of this learning model can serve as an effective strategy for enhancing the quality of education in elementary schools.